Estudo de Schinus terebinthifolius, Anacardium humile e Macairea urundeuva no controle das formigas cortadeiras - Nebo, Liliane (Universidade Federal de São Carlos, 2013)
Leaf-cutting ants are known by their strong power of to pulling down several vegetable crops and to cause economic lost to the agriculture. Several methods have been used for their control such as the use of halogenated, sulfurous and phosphorus compounds. However, the continued use of these compounds leads to problems such as environmental contamination and then raising the needed of new strategies to control of leaf-cutting ants. In this context, this work presents a phytochemical study of the species Schinus terebinthifolius, Anacardium humile e Macairea urundeuva and the insecticide and fungicide potential of the crude extracts, fractions and isolated compounds against the leaf-cutting ants, Atta sexdens rubropilosa, and its symbiotic fungus, Leucoagaricus gongylophorus. The study of these species allowed the isolation and/or identification of several secondary metabolites including triterpens, steroids, flavonoids, biflavonoids, glycosylated flavonoids and phenolic compounds. For both species A. humile and M. urundeuva this is the first report of their chemical composition. From the biological assays with leaf-cutting ants, it was found that several extracts showed insecticidal activity as a result of the synergistic effect of their chemical composition. The elagic acid isolated from M. urundeuva showed activity against the symbiotic fungus of leaf-cutting ants. The metal complexes of flavonoid quercetin didn`t present good results on biological assays against the workers of leaf-cutting ants and its symbiotic fungus. Besides these results, this study contributed to a project that has been developed by the Natural Product Laboratory at UFSCar, which aims to evaluated the biological activity of several metal complexes with different metals and flavonoids to the control of several agriculture pests.
Keywords: Química orgânica; Produtos naturais; Atividade inseticida; Formigas cortadeiras; Leucoagaricus gongylophorus; CIENCIAS EXATAS E DA TERRA::QUIMICA